Regional priorities of foreign trade activity - VLASENKO Ірина; TERNOVA Алла (Ius Modernum, 2025)
Foreign trade activity is an important factor in the development of the countryʼs economy. An urgent issue is the study of the peculiarities of the production and foreign trade activities of the regions of Ukraine in order to outline their opportunities and prospects for development. The purpose of the article is to determine the peculiarities of foreign trade of the Vinnytsia region and the prospects for its development. It is hypothesized that the products of the Vinnytsia region are competitive on the international market, the export dynamics remain positive even during the war, the region has reserves for increasing production and export of products. In the research process, general scientific methods were used: observation, induction and deduction, cause-and-effect relationship, tabular and graphic. The state of trade in goods of the Vinnytsia region in modern conditions has been analyzed. The prospects for the development of priority sectors of the economy of the Vinnytsia region were considered. It is shown that the industry of Vinnytsia region is mainly represented by food, chemical, woodworking and light industry enterprises. Vinnytsia is mainly an agricultural region. The region produces enough food not only to meet its own needs, but also to export products. This applies to both traditional agricultural crops and promising niche crops and organic products. The positive dynamics of the establishment of active foreign trade relations by enterprises of the Vinnytsia region, the growth of export volumes indicates the high competitiveness of the regionʼs products on the international market. A significant share in the structure of exports belongs to raw materials and goods with low added value. In this regard, it is worth focusing attention on the development of industries that produce products with high added value. This task can be achieved through the development of industrial parks, which play an important role in creating new jobs, introducing innovations, contributing to attracting investments, and strengthening the economy of the region. In Vinnytsia, the processing industry, in particular the processing of agricultural products, occupies a significant place in industrial parks. This ensures qualitative growth of the gross regional product, as well as sales markets for agricultural producers.